2004
DOI: 10.1001/archpsyc.61.7.720
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Structural Brain Alterations in Obsessive-Compulsive Disorder

Abstract: The pattern of anatomical features depicted by this voxelwise approach is consistent with data from functional studies. The reported anatomical maps identified the specific parts of the frontostriatal system that were altered in patients with OCD and detected changes in anatomically connected distant regions. These data further define the structural brain alterations in OCD and may contribute to constraining the prevailing biological models of this psychiatric process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
296
7
11

Year Published

2004
2004
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 379 publications
(352 citation statements)
references
References 55 publications
38
296
7
11
Order By: Relevance
“…6 The importance of such investigation is reinforced by studies that described considerable differences in neuroimaging results for different OCD symptom dimensions. 74,75 In summary, gender may be a relevant factor to determine OCD clinical presentation and course, and may be considered to define more homogeneous subgroups. Although the reasons why OCD presentation differs between genders are not clear, one may speculate that they result from both biological and psychosocial influences.…”
Section: Discussionmentioning
confidence: 99%
“…6 The importance of such investigation is reinforced by studies that described considerable differences in neuroimaging results for different OCD symptom dimensions. 74,75 In summary, gender may be a relevant factor to determine OCD clinical presentation and course, and may be considered to define more homogeneous subgroups. Although the reasons why OCD presentation differs between genders are not clear, one may speculate that they result from both biological and psychosocial influences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pujol et al [20] have found reduced gray matter volumes in the medial frontal gyrus, the medial OFC, and the left insulo-opercular region. Similarly, Choi et al [21] have shown volume reduction of the left anterior OFC in patients with OCD.…”
Section: Key Brain Regionsmentioning
confidence: 97%
“…However, in a separate volumetric study from Barcelona, few if any differences were observed. 163 Such preliminary data foreshadow the type of neuroimaging studies that need to be performed in order to validate current dimensional approaches as powerful surrogate indices of neural profiles, or conversely to confirm these brain imaging measures as robust biomarkers of the dimensional phenotypes. In this regard, it is important to emphasize that neuroimaging research could help to refine how the clinical phenotypes are characterized, so as to optimize concordance between clinical phenotypic designations and mediating neural profiles.…”
Section: Endophenotypesmentioning
confidence: 99%